Combustion Characteristics and Flame Stability of a Methane-Air Mixture in Micro-Structured Systems - Chen, Junjie (Engineering Science & Technology, 2022)
Cavities are effective in improving the ability of a flame in micro-structured systems, but the mechanism for increased flame stability remains unclear. Numerical simulations are performed to understand the overall small-scale combustion characteristics of a cavity-stabilized burner. The effects of inlet velocity, equivalence ratio, wall thermal conductivity, channel height, and heat transfer coefficient on flame stability are investigated. A dimensionless number analysis is performed to better understand the heat transfer characteristics of the burner. The results indicate that the cavity structure can induce recirculation of hot products, thereby improving flame stability. The wall thermal conductivity and inlet velocity are vital in determining the flame stability of the burner. Further improvement in flame stability can be achieved using anisotropic walls. Fast flows can cause blowout and slow flows can cause extinction. There exists an optimum inlet velocity for achieving the greatest flame stability. A critical issue in fuel-rich cases is the loss of combustion efficiency. Combustion at the microscale can offer many advantages. Faster ignition and more efficient heat transfer can be achieved, but the design is challenging due to the loss of flame stability.